Immune algorithm-based base station location optimization in the TD-SCDMA network - Ying-jie ZHANG; Ci-ping MAO; Yun-xiao ZU; Xian-you SUN (Tongxin xuebao)
According to the defects of the existing 3G base station location optimization algorithms and the characteris-tics of the TD-SCDMA network, an optimization program was proposed for TD-SCDMA network base station location based on immune algorithm. A mathematical model of base station location was established. A population initialization program based on opposition-based learning and an elite crossover strategy were also designed, and the immune optimi-zation algorithm framework was presented. The experiments' result shows that the algorithm cannot only get higher net-work coverage with a relatively smaller consideration, but also have better convergence.